Losing your dictator: firms during political transition (2020)
We use new firm-level data from Chile to document resource misallocation in favor of politically connected firms during the transition from dictatorship to democracy. We find that firms with links to the Pinochet regime (1973–1990) were relatively unproductive and benefited from resource misallocation under dictatorship, and those distortions persisted into democracy. We show that, after learning that the dictatorship was going to end, firms in the dictator’s network increased their productive capacity, experienced higher profits, and obtained more loans from the main state-owned bank. We test for different explanations and provide suggestive evidence consistent with connected firms aiming to shield their market position for the transition to democracy. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.